UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN MENGGUNAKAN MODEL CIRC (Cooverative Integrated Reading and Composition) DENGAN BANTUAN MEDIA GAMBAR PADA SISWA KELAS IV SDN 002 TANJUNG - Ririn Junita Sari; Iis Aprinawati; Yenni Fitra Surya; Rizki Ananda; Mufarizuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low reading comprehension skills of fourth-grade students in Indonesian language learning. This study aims to improve the reading comprehension skills of fourth-grade students at UPT SDN 002 Tanjung. This study is a classroom action research, conducted in two cycles, with each cycle consisting of two meetings. Based on the results of the research conducted through two cycles, in cycle I meeting 1, the number of students who completed the test was 36.8% with a very low category, and in cycle I meeting 2, the number of students who completed the test was 47.4% with a very low category. In cycle II meeting 1, the number of students who passed increased to 63.2% in the low category, and in cycle II meeting 2, the number of students who passed was 78.9% in the moderate category. Based on the results of this study, it can be seen that the application of the CIRC model with the help of pictures can improve the reading comprehension skills of fourth-grade students at UPT SDN 002 Tanjung in Indonesian language.